Demonstration of a scalable frequency-domain readout of metallic magnetic calorimeters by means of a microwave SQUID multiplexer - Kempf, Sebastian; Wegner, Mathias; Fleischmann, Andreas; Gastaldo, Loredana; Papst, Maximilian; Herrmann, Felix; Richter, Daniel Philipp; Enss, Christian (AIP Advances, 2017)
We report on the first demonstration of a scalable GHz frequency-domain readout of metallic magnetic calorimeters (MMCs) using a 64 pixel detector array that is read out by an integrated, on-chip microwave SQUID multiplexer. The detector array is optimized for detecting soft X-ray photons and the multiplexer is designed to provide a signal rise time τrise<400nsτrise<400nsτrise<400ns and an intrinsic energy sensitivity ϵ<30hϵ<30hϵ<30h. This results in an expected energy resolution ΔEFWHM<10eVΔEFWHM<10eVΔEFWHM<10eV. We measured a signal rise time τriseτriseτrise as low as 90ns90ns90ns and an energy resolution ΔEFWHMΔEFWHMΔEFWHM as low as 50eV50eV50eV for 5.9keV5.9keV5.9keV photons. The rise time is about an order of magnitude faster compared to other multiplexed low-temperature microcalorimeters and close to the intrinsic value set by the coupling between electron and spins. The energy resolution is degraded with respect to our design value due to a rather low intrinsic quality factor of the microwave resonators that is caused by the quality of the Josephson junction of the associated rf-SQUID as well as an elevated chip temperature as compared to the heat bath. Though the achieved energy resolution is not yet compatible with state-of-the-art single-channel MMCs, this demonstration of a scalable readout approach for MMCs in combination with the full understanding of the device performance showing ways how to improve represents an important milestone for the development of future large-scale MMC detector arrays.
Gesehen am 26.03.2018